Pokreti za obnovu jezika u srednjoj Europi: Izrada stručne terminologije u srednjoeuropskim jezicima - Nyomárkay, István (Slavia Centralis, 2020)
Language revitalization movements in Central Europe: the development of technical terminology in Central European languages This article is about the common roots of large Central European linguistic renewal movements among Czechs, Hungarians and Croats. The major principles of word fund enrichment are presented, especially of professional terminology. The mutual influences of Czech, Hungarian and Croatian lexicography are documented. In particular, the cases of lučba (kemija, vegytan, Mischkunst-Scheidekunst), brzojav (Drahtmeldung, sürgöny), prirodopis, prirodoslovlje (Naturkunde, Naturlehre, természetrajz, természettan) have been analyzed.